2018
DOI: 10.1039/c7cp08428e
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective bond scission of methylbenzoate following core excitation

Abstract: The chemical bond scission of methylbenzoate (C6H5CO2CH3) following core excitation at the C and O K edges was examined from partial ion yield measurements across these edges using synchrotron radiation. Site-specific scission of the C-O bonds was observed at both edges. Theoretical X-ray absorption spectra (XAS) were obtained using density functional theory. Peak assignments in the observed spectra were found to be consistent with the theory. From core-excited state dynamics calculations, an elongation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Core-hole states of molecules composed of atoms with low atomic numbers usually decay via Auger processes, yielding a single- or multiple-valence hole state. In the case of core excitation, SSD may be expected if the resulting valence hole is localized in the vicinity of the initial core hole and if the fragmentation precedes energy redistribution. On the contrary, it has been shown that the character of the dicationic state of a molecule after core ionization prevents SSD . Site-specific absorption as such has brought deep insight into charge dynamics with the help of X-ray free-electron laser (FEL) facilities. , …”
mentioning
confidence: 99%
“…Core-hole states of molecules composed of atoms with low atomic numbers usually decay via Auger processes, yielding a single- or multiple-valence hole state. In the case of core excitation, SSD may be expected if the resulting valence hole is localized in the vicinity of the initial core hole and if the fragmentation precedes energy redistribution. On the contrary, it has been shown that the character of the dicationic state of a molecule after core ionization prevents SSD . Site-specific absorption as such has brought deep insight into charge dynamics with the help of X-ray free-electron laser (FEL) facilities. , …”
mentioning
confidence: 99%